Muslim Tatar minorities in the Baltic Sea Region - Svanberg, Ingvar; Westerlund, David (Muslim minorities, 2016)
Preliminary Material /Ingvar Svanberg and David Westerlund -- Introduction /Sebastian Cwiklinski -- Lithuania /Tamara Bairašauskaitė and Egdūnas Račius -- Poland /Agata S. Nalborczyk -- Saint Petersburg /Renat Bekkin and Sabira Ståhlberg -- Finland /Harry Halén and Tuomas Martikainen -- Estonia /Toomas Abiline and Ringo Ringvee -- Latvia /Valters Ščerbinskis -- Sweden /Sabira Ståhlberg and Ingvar Svanberg -- Germany /Sebastian Cwiklinski -- Index /Ingvar Svanberg and David Westerlund.